Fatty acids profile in preterm Colostrum of Tunisian women. Association with selected maternal characteristics. (September 2016) - Fares, S.; Sethom, M.M.; Feki, M.; Cheour, M.; Sanhaji, H.; Kacem, S.; Kaabachi, N.
Abstract: Fatty acids (FA), especially arachidonic (AA, 20:4ω6) and docosahexaenoic (DHA, 22:6ω3) acids are critical for the health and development of infants. Colostrum FA composition has been examined in 101 lactating Tunisian women delivering prematurely using gas chromatography. Among polyunsaturated FA, linoleic acid predominated whereas each of the other polyunsaturated FA accounted for 1% or less of total FA. Colostrum AA and DHA contents were lower in women aged above 34 years compared to those less than 34 years. Preeclampsia was associated with lower DHA (0.40±0.22 vs. 0.53±0.27; p=0.018), but higher AA (1.14±0.44 vs. 0.93±0.30; p<0.006) and AA:DHA ratio (4.31±4.04 vs. 2.29±2.79; p<0.001). In multivariate analysis, colostrum DHA correlated with plasma DHA (β, 0.417; p=0.002), maternal age (β, −0.290; p=0.028) and preeclampsia (β, −0.270; p=0.042). Preterm colostrum FA profile in Tunisian women is comparable to those of other populations. Colostrum AA and DHA levels are altered in aged and pre-eclamptic women. Highlights: Fatty acids profile in preterm colostrum from 101 Tunisians women is reported. The profile is characterized by richness in saturated and monounsaturated fatty acids and a relatively high w6:w3 ratio. DHA was decreased while AA and w6:w3 ratio were increased and in preterm colostrums from pre-eclamptic women. Advanced maternal age, low plasma DHA and preeclampsia are the main risk factors for decreased DHA in colostrum.